Contiguous Metastasis of Pulmonary Adenocarcinoma to Meningioma - Nakaya, Masato; Ichimura, Shinya; Kurebayashi, Yutaka; Mochizuki, Youichi; Fukaya, Raita; Fukuchi, Masahito; Fujii, Koji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Metastasis from one tumor into another is known as tumor-to-tumor metastasis. We report a case of a contiguous occurrence of meningioma and brain cancer metastasis.Patient A 91-year-old woman presented with a sudden onset of weakness in her right limbs and gait disturbance. Fourteen years previously, she had a tumor that was suspected to be a meningioma in the left frontal convexity with no change for several years. One year earlier to presentation she was diagnosed with lung carcinoma in the left lower lobe.Results Magnetic resonance images revealed enlargement of the tumor with perifocal edema. Histologic examination showed a meningioma with contiguous metastatic poorly differentiated adenocarcinoma, as well as a clearly defined border between the two components. The clinical origin of the metastasis was presumed to be from the left lower lobe of the lung.Conclusion Although our case does not strictly fulfill the definition of tumor-to-tumor metastasis, we suggest a contiguous occurrence develops by the same mechanism and may be a subtype of this process. Although previous reports suggested the loss of epithelial cadherin (E-cadherin) expression in the recipient tumor as the cause of contiguous metastasis, E-cadherin expression was positive in our case and did not seem to be involved in the localization of the metastasis.
Keywords: adenocarcinoma; contiguous metastasis; E-cadherin; meningioma; tumor-to-tumor metastasis